Defining a threshold for intervention in breast cancer-related lymphedema: What level of arm volume increase predicts progression? - Specht, Michelle C (2013)
PURPOSE: Evaluate arm volume measurements and clinico-pathologic characteristics of breast cancer patients to define a threshold for intervention in breast cancer-related lymphedema. METHODS: We prospectively performed arm volume measurements on breast cancer patients using a Perometer. Arm measurements were performed pre- and post-operatively, and change in arm volume was quantified using a relative volume change (RVC) equation. Patient and treatment risk factors were evaluated. Cox proportional hazards models with time-dependent covariates for RVC were used to evaluate whether RVC elevations of ≥3%-<5% or ≥5%-<10% occurring ≤3 months or >3 months after surgery were associated with progression to ≥10% RVC. RESULTS: 1173 patients met eligibility criteria with a median of 27 months post-operative follow-up.The cumulative incidence of ≥10% RVC at 24 months was 5.26% (95% CI: 4.01% – 6.88%). By multivariable analysis, a measurement of ≥5-<10% RVC occurring >3 months after surgery was significantly associated with an increased risk of progression to ≥10% RVC (HR: 2.97, p<0.0001), but a measurement of ≥3-<5% RVC during the same time period was not statistically significantly associated (HR: 1.55, p=0.10). Other significant risk factors included a measurement ≤3 months after surgery with RVC of ≥3–<5% (p=0.007), ≥5–<10% (p<0.0001), or ≥10% (p=0.023), axillary lymph node dissection (ALND) (p<0.0001), and higher BMI at diagnosis (p=0.0028). Type of breast surgery, age, number of positive or number of lymph nodes removed, nodal radiation, chemotherapy, and hormonal therapy were not significant (p>0.05). CONCLUSION: Breast cancer patients who experience a relative arm volume increase of ≥3%-<5% occurring >3 months after surgery do not have a statistically significant increase in risk of progression to ≥10%, a common lymphedema criterion . Our data supports utilization of a ≥5-<10% threshold for close monitoring or intervention, warranting further assessment. Additional risk factors for progression to ≥10% include ALND, higher BMI, and post-operative arm volume elevation.